An Analytical Review of Existing Supermarket Billing Systems - Ocen, Gilbert; Semwogerere, Twaibu; Sekamwa, Umar; Matovu, Davis (East African Nature and Science Organization, 2021)
Retail shops and stores form part of the nation’s business sector involved in selling and providing several goods and services. The main objective was to study and analyse existing supermarket billing systems and possibly identify their weaknesses and strengths. This will enable us to generate an RFID billing system that is unique and even more advantageous than the existing systems. The methodology used was qualitative involving hard and soft document reviews and observational experiments. Findings revealed that there are several billing systems which include the manual price tag system where a mini-computer (calculator) is used to sum up the total bill per customer at a time, the barcode reader system, the smart chart with store cards, and the ‘smart shopping cart. It was noted that these have the advantage of giving confidence all the items are counted, paid for, save time and are cheap to use. However, they are also associated with several weaknesses like long waiting time (queues), the systems require a lot of human effort to read the barcodes which is not efficient, barcode systems sometimes fail to read, possible human errors while entering information, possible cheating through wrongly-fed information and the desynchronization effects because of the unreliable network. This was an awareness drive about the existing supermarket billing systems in order to enhance further studies on better ones